2011
DOI: 10.1038/ejhg.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of bioinformatics predictions and functional splicing assays to the interpretation of unclassified variants of the BRCA genes

Abstract: A large fraction of sequence variants of unknown significance (VUS) of the breast and ovarian cancer susceptibility genes BRCA1 and BRCA2 may induce splicing defects. We analyzed 53 VUSs of BRCA1 or BRCA2, detected in consecutive molecular screenings, by using five splicing prediction programs, and we classified them into two groups according to the strength of the predictions. In parallel, we tested them by using functional splicing assays. A total of 10 VUSs were predicted by two or more programs to induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
101
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 27 publications
(42 reference statements)
15
101
0
1
Order By: Relevance
“…These programs have been extensively used by other groups and proved their usefulness for the predictions of splicing defects. 14,15,31 To make in vivo/in vitro assessments of a variant true impact on splicing, the analysis of patient RNA is ideal but the availability of disease relevant material is often limited, especially for neurological disorders like ASD and SCZ for which brain biopsies are rare. The minigene approach allows the rapid testing of any variant and it circumvents the problems associated with the difficult access to patient RNA (from patients' derived biopsies, immortalized cell lines or blood sample recollection several years after the original recruitment).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These programs have been extensively used by other groups and proved their usefulness for the predictions of splicing defects. 14,15,31 To make in vivo/in vitro assessments of a variant true impact on splicing, the analysis of patient RNA is ideal but the availability of disease relevant material is often limited, especially for neurological disorders like ASD and SCZ for which brain biopsies are rare. The minigene approach allows the rapid testing of any variant and it circumvents the problems associated with the difficult access to patient RNA (from patients' derived biopsies, immortalized cell lines or blood sample recollection several years after the original recruitment).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it also helps to overcome challenges like low level of expression in blood cells of genes involved in neurodevelopmental diseases, and the masking effect of preferential amplification of the wild-type allele. As an alternative, we and others showed that using monoallelic minigene is a powerful tool to assess the impact of sequence variants on splicing in vitro, 14,15,32 as high correlation is observed between minigene results and patient RNA analysis. Among the 14 variants predicted to affect splicing by different programs and thus tested through the functional splicing assay, 29% (4/14) had an actual effect on splicing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for diagnostic mutation screening of the BRCA2 gene in patients were applied according to the current French recommendations. Screening for BRCA2 mutations was performed as previously described 16. Informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the BRCA2 c.520C>T variant induces exon 7 skipping 16. Here, we investigated the effects on splicing of seven additional VUS located in this exon and identified four new splicing mutations.…”
Section: Introductionmentioning
confidence: 99%